Pattern of Brain Injury in Patients With Thrombotic Thrombocytopenic Purpura in the Precaplacizumab Era. Issue 10 (24th June 2021) - Mirouse, Adrien; Legriel, Stéphane; Dumas, Guillaume; Labro, Guylaine; Veyradier, Agnès; Zafrani, Lara; Valade, Sandrine; Hourmant, Yannick; Boutboul, David; Darmon, Michael; Coppo, Paul; Mariotte, Eric; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe short- and long-term neurologic prognosis of patients with thrombotic thrombocytopenic purpura and to identify clusters associated with evolution. DESIGN: Prospective French cohort. SETTING: ICU in a reference center. PATIENTS: All consecutive patients with newly diagnosed thrombocytopenic purpura. INTERVENTION: Comprehensive clinical, biological, and radiological evaluation at admission. Neurocognitive recovery was assessed using Glasgow Outcome Scale (range 1–5, with 1 representing death and 5 representing no or minimal neurologic deficit). MEASUREMENTS AND MAIN RESULTS: Among the 130 newly diagnosed patients with thrombocytopenic purpura, 108 (83%; age 43 [30–52]; 73% women) presented with neurologic signs, including headaches (51%), limb weakness, paresthesia, and/or aphasia (49%), pyramidal syndrome (30%), decreased consciousness (20%), seizure (19%), cognitive impairment (34%), cerebellar syndrome (18%), and visual symptoms (20%). A hierarchical cluster analysis identified three distinct groups of patients. Cluster 1 included younger patients (37 [27–48], 41 [32–52], and 48 [35–54], in clusters 1, 2 and 3, respectively; p = 0.045), with a predominance of headaches (75%, 27%, and 36%; p < 0.0001). Cluster 2 patients had ataxic gait and cerebellar syndrome (77%, 0%, and 0%; p < 0.0001) and dizziness (50%, 0%, and 0%; p < 0.0001). Cluster 3 included patients with delirium (36%, 0%, and 9%; p < 0.0001), obtundation (58%, 0%, and 24%; p < 0.0001), and seizure (36%, 0%, and 14%; p < 0.0001). Acute kidney injury was 32%, 68%, and 77%, in clusters 1, 2, and 3, respectively ( p < 0.0001). The three clusters did not differ for other biological or brain imaging. After a median follow-up of 34 months (12–71 mo), 100 patients (93%) were alive with full neurocognitive recovery (i.e., Glasgow Outcome Scale score 5) in 89 patients (89%). Patients from cluster 1 more frequently exhibited full recovery (Glasgow Outcome Scale score of 5) compared with clusters 2 and 3, (44 [98%], 13 [65%], and 21 [60%] at 3 mo; p < 0.0001), (44 [100%], 15 [68%], and 23 [69%] at 6 mo; p < 0.0001), and (40 [100%], 15 [79%], and 20 [57%] at 1 yr; p < 0.0001). CONCLUSIONS: Initial clinical neurologic evaluation in thrombocytopenic purpura patients distinguishes three groups of patients with different clinical and functional outcomes.